Pengaruh Hot Water Extraction terhadap Sudut Kontak Octomeles sumatrana dan Duabanga moluccana dan Kaitannya terhadap Zat Ekstraktif dan Struktur Anatomi Kayu: Effect of Hot Water Extraction on Contact Angle of Octomeles sumatrana and Duabanga moluccana Woods and Its Correlation to the Extractive Content and Anatomical Structure - Marbun, Sari Delviana; Wahyudi, Imam; Suryana, Jajang; Nawawi, Deded Sarip; Ratih, Damayanti; Silaban, Rosalia (PERENNIAL, 2025)
Binuang bini (Octomeles sumatrana) and binuang laki (Duabanga moluccana) are fast growing species that have the potential to be developed as engineered wood products. However, previous studies have shown that both wood species have high contact angle values due to the extractive content and the high acidity. Therefore, this study aimed to examine the effect of hot water extraction (HWE) pretreatment to eliminate these limiting factors. The results proved that HWE pretreatment statistically significantly decreased the contact angle of binuang bini wood but not for binuang laki wood. HWE pretreatment resulted in a decrease in the levels of hot water-soluble extractive content and degradation of other wood chemical components. The different effectiveness of HWE pretreatment on binuang bini and binuang laki wood on improving the contact angle is influenced by differences in the quantity and quality of extractive substances as well as differences in the anatomical structure characteristics of these species.